Effects of exposure to alcohol‐related cues on racial discrimination. (16th October 2017) - Stepanova, Elena V.; Bartholow, Bruce D.; Saults, J. Scott; Friedman, Ronald S.
Abstract: Prior research has shown that exposure to alcohol‐related images exacerbates expression of implicit racial biases, and that brief exposure to alcohol‐related words increases aggressive responses. However, the potential for alcohol cue exposure to elicit differential aggression against a Black (outgroup) relative to a White (ingroup) target—that is, racial discrimination—has never been investigated. Here, we found that White participants ( N = 92) exposed to alcohol‐related words made harsher judgments of a Black experimenter who had frustrated them than participants who were exposed to nonalcohol words. These findings suggest that exposure to alcohol cues increases discriminatory behaviors toward Blacks.